Correlation between Academic Achievement Results and Students' Perceptions in Instant Response System-Based Language Learning Classes at the University - Tae-Jin Koh; Yong-Jeong Kim (MDPI AG, 2024)
In the contemporary university environment, there is a growing trend towards the use of innovative pedagogical methods aimed at increasing student engagement and learner-centeredness. Despite this shift, traditional lecture formats continue to be used, particularly in large classes or language courses. This is largely due to the perceived efficiency and convenience of the traditional lecture format for both teachers and students. However, the limited interaction and communication inherent in traditional lectures can hinder student satisfaction and participation. To address this, the integration of an instant response system (IRS) into the classroom environment offers a promising solution. These systems, which leverage technology and anonymity, facilitate real-time feedback and active student participation without placing a significant burden on the instructor. This study examines the implementation of IRSs in Hindi language learning courses at Hankuk University of Foreign Studies, Seoul, focusing on their impact on student satisfaction, engagement, and self-efficacy at different levels of academic achievement. The findings reveal nuanced differences in perceptions and outcomes between high, average, and low achievers, highlighting the potential of IRSs to foster engagement and communication in diverse learner cohorts. Contrary to expectations, satisfaction levels did not consistently correlate with academic performance. In fact, middle achievers showed significant benefits. Qualitative findings further elucidate students' experiences and highlight the importance of tailored approaches to maximize the effectiveness of IRSs. Overall, this research highlights the adaptability and effectiveness of IRSs in promoting active learning environments, and offers valuable implications for instructional design and pedagogical practice.